2020
DOI: 10.3390/electronics10010029
|View full text |Cite
|
Sign up to set email alerts
|

LTPS TFTs with an Amorphous Silicon Buffer Layer and Source/Drain Extension

Abstract: A low leakage poly-Si thin film transistor (TFT) is proposed featuring hydrogenated amorphous silicon (a-Si:H) buffer layer and source/drain extension (SDE) by using technology computer aided design (TCAD) simulation. This architecture reduces off-current effectively by suppressing two leakage current generation mechanisms with little on-current loss. The amorphous silicon buffer layer having large bandgap energy (Eg) suppresses both thermal generation and minimum leakage current, which leads to higher on/off … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Through electrical measurements, an off-state leakage is found, which is also known as the gate-induced drain leakage (GIDL) current [38][39][40]. Previous studies based on planar structure have reported that the GIDL current results from the trap-assisted tunneling model induced by the grain boundary of the channel [38,41,42]. In this work, the GIDL current is increased with the drain bias increasing.…”
mentioning
confidence: 92%
“…Through electrical measurements, an off-state leakage is found, which is also known as the gate-induced drain leakage (GIDL) current [38][39][40]. Previous studies based on planar structure have reported that the GIDL current results from the trap-assisted tunneling model induced by the grain boundary of the channel [38,41,42]. In this work, the GIDL current is increased with the drain bias increasing.…”
mentioning
confidence: 92%
“…The three main parts of TFT include the active channel layer, the insulating layer and the electrode material, wherein the active channel layer material plays a key role in the fabrication of high-quality TFTs. Various materials, such as hydrogenated amorphous silicon (a-Si:H), polycrystalline silicon (poly-Si) and organic semiconductors, have been used as the active channel layer for the fabrication of TFTs [3][4][5]. However, the Si-based TFTs possess an inherent limitation: they are opaque in the visible wavelength region, which results in the reduction of light transmittance and brightness for the display [6].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the mainstream television resolution is 2K, while 4K is the next generation mainstream television technology [ 5 , 6 ]. However, when the resolution increases from 2K to 4K, the resistance and capacitance loading (RC loading) in the scan lines of the displays will increase significantly [ 7 , 8 , 9 , 10 ]. Therefore, it is a challenge to design these displays with a 4K resolution because the rising time is rather long.…”
Section: Introductionmentioning
confidence: 99%